The level of awaraness of the society towards the environment and the level of action taken by the society to preserve the environment / Mohamad Danial Mohd Jailani…[et.al] - Mohd Jailani, Mohamad Danial; Abdul Salim, Fatin Athirah; Mohd Fauzi, Siti Nurfarahhin; Osman, Muhammad Firhan (Faculty of Communication & Media Studies, 2019)
Day by day, Malaysia will be announced with the issues regarding our environmental pollution through newspaper, social medias, television and more media platform. The government have tried their best to promote and raise the awareness to the public but at the end of the day, only the public can change the mentality by taking action towards all the environmental issues. Therefore, this research is conducted in order to find the level of awareness towards the environment and to identify the level of action taken by the society to preserve it nowadays. This study involved 662 respondents and the respondents were gained from on online survey through Google Survey Form. The form has been distributed to social medias and from that platform, we gained all the respondents and used that as data collection. At the end, we knew that Malaysia still have a very high level of awareness towards the environment but as for the level of action taken to preserve it is still low. Therefore, Malaysia needs to do something to make sure the next generation will be able to experienced all the green environments that we have today.